2002
DOI: 10.1111/j.1574-6941.2002.tb00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of bacteria from Pinus sylvestris–Suillus luteus mycorrhizas and their effects on root–fungus interactions and plant growth

Abstract: Bacteria from Pinus sylvestris-Suillus luteus mycorrhizas were isolated, characterised, and their effects on P. sylvestris-S. luteus interactions and plant growth investigated in vitro. The isolates formed five distinct phenotypic and physiological groups. Two of the groups, accounting for 34 of the 55 isolates, consisted of Bacillus spp., with three subgroups represented. The other groups contained Burkholderia spp., Serratia spp. and Pseudomonas spp. Representatives from each bacterial group were used in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Bending et al ( 2002 ) also demonstrated that Pseudomonas isolates stimulated lateral root formation similar to our results. In total, these results suggest a diversity of growth promoting mechanisms operating on plant or fungi and/or both and illustrate the complexity of the evolving MHB concept.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bending et al ( 2002 ) also demonstrated that Pseudomonas isolates stimulated lateral root formation similar to our results. In total, these results suggest a diversity of growth promoting mechanisms operating on plant or fungi and/or both and illustrate the complexity of the evolving MHB concept.…”
Section: Discussionsupporting
confidence: 92%
“…Poole et al ( 2001 ) reported that bacteria ( Burkholderia and Pseudomonas ) isolated from Pinus sylvestris — Lactarius rufus mycorrhizas did not affect the total number of roots formed by the plants but only ectomycorrhizal formation. While Bending et al ( 2002 ) found bacteria isolates ( Burkholderia spp., Serratia spp., Pseudomonas spp., and Bacillus spp.) from Pinus sylvestris — Suillus luteus mycorrhizas stimulating root growth and even shoot growth by Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the bOTU richness of Firmicutes was higher in Tm -dominant soil. Firmicutes contains the genera Bacillus , Cohnella , and Paenibacillus , which are commonly found in mycorrhiza-associated environments [6365]. Therefore, higher richness of Firmicutes may suggest a conserved trait associated with fungi-bacteria interaction or resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genera were previously detected in the fairy ring of T . matsutake [13, 15], and are commonly found in the rhizosphere or mycorrhizosphere [6365, 73]. In addition, these taxa may be similar on a functional level.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the hyphal network at the base of fungal fruiting bodies on the local bacterial community structure in natural soil has, as far as we know, never been described in detail by a fingerprinting technique such as DGGE. Most research in this area so far has focused on specific groups of culturable bacteria selected under the influence of a certain fungus and not on bacterial community analyses (Frey et al, 1997;Bending et al, 2002;Rangel-Castro et al 2002;Tornberg et al 2003). Hence, for the first time we reveal a glimpse of an ecological effect on soil bacterial communities brought about by emerging fungal structures and presumably related to upshifts in growth-enhancing ecological opportunities for bacterial associates.…”
Section: Discussionmentioning
confidence: 99%